MDPSK-based nonequalization OFDM for coherent free-space optical communication - Chen, Chen (2014)
In this letter, we apply a non-equalization orthogonal frequency-division multiplexing (NE-OFDM) technique in optical turbulence channel for coherent free-space optical (FSO) systems, utilizing multilevel differential phase-shift-keying (MDPSK). We adopt the modified Rician distribution as the optical turbulence channel for coherent FSO systems, where both amplitude fading and phase distortion are taken into consideration. The differential encoding process of MDPSK based NE-OFDM can be performed either in the frequency domain (FD) or in the time domain (TD). Our simulation results show that NE-OFDM using FD-MDPSK achieves nearly the same bit-error-rate (BER) performance as that using TD-MDPSK, but with a relatively lower hardware complexity and a higher spectral efficiency. It is also revealed that FD-MDPSK based NE-OFDM attains a comparable BER performance to the conventional OFDM with pilot tones or training sequences assisted channel estimation and equalization. Hence, FD-MDPSK based NE-OFDM is promising for coherent FSO communication.